Disease Characteristics, Care-Seeking Behavior, and Outcomes Associated With the Use of AYUSH-64 in COVID-19 Patients in Home Isolation in India: A Community-Based Cross-Sectional Analysis - Srikanth, Narayanam; Kumar, Adarsh; Chandrasekhararao, Bhogavalli; Singhal, Richa; Yadav, Babita; Khanduri, Shruti; Jameela, Sophia; Rai, Amit Kumar; Tripathi, Arunabh; Rana, Rakesh; Ahmad, Azeem; Sharma, Bhagwan Sahai; et al. (Frontiers in Public Health, 2022)
Background: During the second wave of the COVID-19 pandemic in India, the Ministry of Ayush, conducted a community study to provide therapeutic care to asymptomatic, mild, and moderate COVID-19 patients in home isolation based on the empirical evidence generated on the efficacy of AYUSH-64 in COVID-19. Objective: To document disease characteristics, care-seeking behavior, and outcomes in asymptomatic, mild, or moderate COVID-19 patients in home isolation, who used AYUSH-64 for COVID-19. Methods: Cross-sectional analysis of the data generated through a community study conducted in India, from May 08 to August 31, 2021 was performed to study the disease characteristics, care-seeking behavior during home isolation, clinical outcomes, adverse events, and the association between various risk factors and clinical recovery during the study period. The data was collected through semi-structured questionnaires, available in electronic data collection format at baseline, day 7, 14, and 21 and logistic regression was performed to explore the relationship between relevant variables, and clinical recovery. Results: Data from 64,642 participants was analyzed for baseline assessment and final analysis was done for 49770 participants. The mean age of the enrolled participants was 38.8±11.7 years and 8.4% had co-morbidities. AYUSH-64 was utilized as an add-on to the standard care by 58.3% participants. Comparable clinical outcomes were observed in participants who were utilizing AYUSH-64 either as standalone or as add-on to standard care, in terms of clinical recovery, disease progression, requirement for oxygen supplementation, hospitalization, ICU admission, and need for ventilator support. Younger age, having no co-morbidities or substance abuse, and having vaccinated were associated with early clinical recovery than those who were older and not vaccinated. Conclusions: The findings of the study assert that AYUSH-64 use, either as stand-alone or as an adjunct to standard care in asymptomatic, mild, or moderate COVID-19, is associated with good clinical outcomes. Ayush services and interventions can be effectively integrated into the mainstream public health architecture to serve public health goals.